"\\left( {1 - {x^2}} \\right)\\frac{{dy}}{{dx}} - {x^2}y = \\left( {1 + x} \\right)\\sqrt {1 - {x^2}}"
"y' - \\frac{{{x^2}}}{{1 - {x^2}}}y = \\frac{{\\left( {1 + x} \\right)\\sqrt {1 - {x^2}} }}{{\\left( {1 - {x^2}} \\right)}}"
Let
"y = uv \\Rightarrow y' = u'v + uv'"
Then
"u'v + uv' - \\frac{{{x^2}}}{{1 - {x^2}}}uv = \\frac{{\\left( {1 + x} \\right)\\sqrt {1 - {x^2}} }}{{\\left( {1 - {x^2}} \\right)}}"
"u'v + u\\left( {v' - \\frac{{{x^2}}}{{1 - {x^2}}}v} \\right) = \\frac{{\\left( {1 + x} \\right)\\sqrt {1 - {x^2}} }}{{\\left( {1 - {x^2}} \\right)}}"
Let
"v' - \\frac{{{x^2}}}{{1 - {x^2}}}v = 0 \\Rightarrow \\frac{{dv}}{{dx}} = \\frac{{{x^2}}}{{1 - {x^2}}}v \\Rightarrow \\frac{{dv}}{v} = \\frac{{{x^2}}}{{1 - {x^2}}}dx = \\left( {\\frac{1}{{2(x + 1)}} - \\frac{1}{{2(x - 1)}} - 1} \\right)dx \\Rightarrow \\ln v = \\frac{1}{2}\\ln (x + 1) - \\frac{1}{2}\\ln (1 - x) - x \\Rightarrow \\ln v = \\ln \\sqrt {\\frac{{1 + x}}{{1 - x}}} - x \\Rightarrow v = {e^{\\ln \\sqrt {\\frac{{x + 1}}{{1 - x}}} - x}} = {e^{ - x}}\\sqrt {\\frac{{x + 1}}{{1 - x}}}"
Then
"u'{e^{ - x}}\\sqrt {\\frac{{x + 1}}{{1 - x}}} = \\frac{{\\left( {1 + x} \\right)\\sqrt {1 - {x^2}} }}{{\\left( {1 - {x^2}} \\right)}} \\Rightarrow u' = {e^x}\\frac{{(1 + x)\\sqrt {1 - {x^2}} }}{{\\left( {1 - {x^2}} \\right)}}\\sqrt {\\frac{{1 - x}}{{x + 1}}} = {e^x}\\frac{{\\sqrt {(1 - x)(1 + x)} }}{{\\left( {1 - x} \\right)}}\\sqrt {\\frac{{1 - x}}{{x + 1}}} = {e^x} \\Rightarrow u = {e^x} + C"
Then
"y = uv = \\left( {{e^x} + C} \\right){e^{ - x}}\\sqrt {\\frac{{x + 1}}{{1 - x}}} = \\sqrt {\\frac{{x + 1}}{{1 - x}}} + C{e^{ - x}}\\sqrt {\\frac{{x + 1}}{{1 - x}}}"
Answer: "y = \\sqrt {\\frac{{x + 1}}{{1 - x}}} + C{e^{ - x}}\\sqrt {\\frac{{x + 1}}{{1 - x}}}"
Comments
Leave a comment